2021
DOI: 10.1128/mbio.03196-20
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between Plasticity and Velocity in Mycelial Growth

Abstract: Tip-growing fungal cells maintain cell polarity at the apical regions and elongate by de novo synthesis of the cell wall. Cell polarity and tip growth rate affect mycelial morphology. However, it remains unclear how both features act cooperatively to determine cell shape. Here, we investigated this relationship by analyzing hyphal tip growth of filamentous fungi growing inside extremely narrow 1 μm-width channels of microfluidic devices. Since the channels are much narrower than the diameter of hyphae, any hyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…This relationship between hyphal diameter and extension rate has been predicted by the vesicle supply center model ( equation 2 ) ( 5 ), and our results establish that this relationship holds upon specific perturbation of the Spitzenkörper. Interestingly, it was recently shown that variation in hyphal width and extension rate increases in faster and wider growing species ( 49 ), suggesting that the regulation of growth may be less precise when growth speeds increase. Together, our results reveal that the Spitzenkörper component Mlc1 links hyphal growth and morphology, suggesting that this structure is critical for minimizing growth and morphology variation in a fungal population, which is likely to be important for mycelium development.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between hyphal diameter and extension rate has been predicted by the vesicle supply center model ( equation 2 ) ( 5 ), and our results establish that this relationship holds upon specific perturbation of the Spitzenkörper. Interestingly, it was recently shown that variation in hyphal width and extension rate increases in faster and wider growing species ( 49 ), suggesting that the regulation of growth may be less precise when growth speeds increase. Together, our results reveal that the Spitzenkörper component Mlc1 links hyphal growth and morphology, suggesting that this structure is critical for minimizing growth and morphology variation in a fungal population, which is likely to be important for mycelium development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Podospora anserina have, for example, shown that narrow hyphae are developed during fungal growth in order to breach cellulosic substrates such as cellophane [32]. Additionally, recent elegant studies of hyphal morphological adaptation to occupy extremely narrow channels suggest that a trade-off may exist between plasticity and velocity in hyphal growth [33]. These observations provide evidence that generation of specialised hyphae-derived structure for invasive growth may be a conserved mechanism in filamentous fungi.…”
Section: What Is a Transpressorium?mentioning
confidence: 91%
“…Although human infectious fungi do not utilize special infection structures like appressoria for invasion, the inability of A. fumigatus aseptate hyphae to invade murine lung tissue could be from lack of turgor pressure in the tip compartment required for physical invasion. A recent study exploring the connections between hyphal growth and polarity maintenance has found filamentous fungal organisms with fast growing hyphal tips and high turgor pressure to often lose polarity when undergoing invasive growth (i.e., penetration into small spaces) [77]. in contrast, slow growing fungi with lower turgor pressure are able to maintain a single polarized growth axes under the same conditions.…”
Section: Plos Pathogensmentioning
confidence: 99%